ANALISIS KONFLIK KEBIJAKAN TARIF PARKIR DI PASAR ANGSO DUO KOTA JAMBI: PENDEKATAN RETRIBUSI DAN MANAJEMEN KOMUNITAS - Aflah Rasyid Ridho; Maulana Mukhlis; Feni Rosalia; Pitojo Budiono (Halu Oleo University, 2025)
This article discusses the issues of illegal parking and street-level extortion at Pasar Angso Duo, Jambi, caused by poorly managed parking fee policies. The public is burdened with dual payments, paying official parking fees while still facing illegal levies from irresponsible individuals. This situation leads to public dissatisfaction and has the potential to trigger social conflicts. This study uses a conflict management approach to analyse the causes, impacts, and possible solutions to these issues. The findings indicate that weak oversight and enforcement of parking policies are the primary factors behind the emergence of illegal parking and street-level extortion. Moreover, the government has been ineffective in managing conflicts involving various stakeholders, such as the public and informal groups. To address these issues, the study recommends that the government enhance monitoring, empower the community by forming parking management cooperatives or workgroups, and implement a more assertive legal approach to combat extortion. Additionally, providing skill training and alternative employment opportunities for those involved in illegal parking can help prevent future conflicts. By implementing these solutions, it is expected that the illegal parking and extortion issues at Pasar Angso Duo can be effectively addressed, creating a safe and conducive market environment.